(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In the years of independence, the role and role of local state authorities in the organization of election processes in Uzbekistan, the directions of activities of local governments in the organization of political processes are highlighted. Also, the tasks of regional, district and city hokims related to the establishment of precinct election commissions, collecting voters and other relevant information, providing other organizational and technical support to election commissions by hokims are indicated on the basis of sources.